Visual evoked potentials in the diagnosis of optic neuropathies: a literature review (Ukrainian Journal of Ophthalmology, 2025)
This review analyzes the utility of visual evoked potentials (VEP) as a method for visual function assessment in optic neuropathies. We systematically reviewed the existing data on the application of several types of VEP (pattern-reversal, pattern-onset/offset, flash-pattern, and chromatic) for objective assessment of the visual pathway in inflammatory, demyelinating, ischemic, toxic, compressive and traumatic optic neuropathies. The review presents the typical changes in VEP parameters (latency, amplitude and morphology) for each of the pathologies considered, and their relationships with clinical manifestations and results of other neuroophthalmological examination techniques such as perimetry and optical coherence tomography. The paper highlights the diagnostic and differential diagnostic value of VEP, especially in challenging cases and for providing an objective approach for characterizing visual function deficiencies.
Keywords: optic neuropathy; visual evoked potentials; electroretinography